From Victorian Buildings to the Victorian Built Heritage: Victorian studies and the Re-interpretation of 19th-century architecture - Isabelle Cases (Cahiers Victoriens et Edouardiens)
This paper addresses the question of the limits and frontiers of Victorian studies through the particular example of the study of Victorian architecture. First of all, working on Victorian architecture implies focussing on different fields and methodologies. Art history is an obvious first step, and indeed a necessary but difficult approach due to the constant reinterpretation of styles of the past and the discovery of new exotic models in the Victorian period, which resulted in the so-called Victorian architectural eclecticism. On the other hand, the multiplication of debates in essays and architectural journals—which reveal, among others, a new but uneasy relationship between architecture and engineering—as well as the many personal testimonies and experiences of the new architectural environment provide fascinating and indispensable primary sources. Victorian architecture illustrates industrial and social evolutions in the 19th century which can be traced in general trends, more specific examples or even sometimes particular details. The specificity of Victorian architecture, however, also lies in the fact that it still constitutes a large part of Britain’s built heritage today. Not only many famous buildings, churches, stations, but also whole streets, districts or aspects of urban planning date back to the Victorian period. Studying Victorian architecture therefore necessarily implies engaging physically with the Victorian architectural and industrial heritage and, as a consequence, with its interpretation, renovation and possibly its adaptive reuse. One can wonder what is lost and what is found in that coming and going from the 19th-century reality of Victorian buildings to the numerous issues and challenges set by the Victorian architectural heritage in the 21st century. What are the risks for a specialist of the Victorian period of blurring interpretations? Or do we have here an opportunity to use neo-Victorian approaches and experiences to shed new lights on why the architectural question is so important to an understanding of the Victorians and therefore to re-engage more forcefully in, rather than disengage from, Victorian studies?